Multi-wavelength Raman lidar, sun photometric and aircraft measurements in combination with inversion models for the estimation of the aerosol optical and physico-chemical properties over Athens, Greece - Papayannis, Alexandros D.; Amiridis, Vassilis; Mamouri, Rodanthi-Elisavet (My University, 2012)
A novel procedure has been developed to retrieve, simultaneously, the optical, microphysical and chemical properties of tropospheric aerosols with a multi-wavelength Raman lidar system in the troposphere over an urban site (Athens, Greece: 37.9° N, 23.6° E, 200 m a.s.l.) using data obtained during the European Space Agency (ESA) THERMOPOLIS project, which took place between 15-31 July 2009 over the Greater Athens Area (GAA). We selected to apply our procedure for a case study of intense aerosol layers that occurred on 20-21 July 2009. The National Technical University of Athens (NTUA) EOLE 6-wavelength Raman lidar system has been used to provide the vertical profiles of the optical properties of aerosols (extinction and backscatter coefficients, lidar ratio) and the water vapor mixing ratio. An inversion algorithm was used to derive the mean aerosol microphysical properties (mean effective radius (r eff), single-scattering albedo ω) and mean complex refractive index (m)) at selected heights in the 2-3 km height region. We found that reff was 0.14-0.4 (±0.14) μm, ω; was 0.63-0.88 (±0.08) (at 532 nm) and m ranged from 1.44 (±0.10) + 0.01 (±0.01)i to 1.55 (±0.12) + 0.06 (±0.02)i, in good agreement (only for the reff values) with in situ aircraft measurements. The water vapor and temperature profiles were incorporated into the ISORROPIA II model to propose a possible in situ aerosol composition consistent with the retrieved m and ω values. The retrieved aerosol chemical composition in the 2-3 km height region gave a variable range of sulfate (0-60%) and organic carbon (OC) content (0-50%), although the OC content increased (up to 50%) and the sulfate content dropped (up to 30%) around 3 km height; the retrieved low ω value (0.63), indicates the presence of absorbing biomass burning smoke mixed with urban haze. Finally, the retrieved aerosol microphysical properties were compared with column-integrated sun photometer CIMEL data.
Keywords: Aerosols; Photometry; Troposphere; Albedo; Open access publishing